أهداف التنمية المستدامة في إطار (الاجندة المحلية 21) وتحليل قدرة السلطات المحلية السورية على تحقيقها - فضلية, عابد (Latakia University Journal - Economic and Legal Sciences Series, 2019)
شددت الأمم المتحدة منذ مؤتمر (استوكهولم) عام (1972) ومؤتمرات قمة الأرض اللاحقة, على جدلية التلازم بين (التنمية الاقتصادية) و(التوازن البيئي). وفي هذه المؤتمرات تعهدت سورية بوضع خطط وطنية في مجال البيئة والتنمية المستدامة يطلق عليها اسم (الأجندة المحلية 21), والتي يتطلب تنفيذها تكاملاً تخطيطياً وتنموياً, والأهم تعاوناً وتشاركيةً مرنةً وشفافة بين السلطات والأجهزة الإدارية الحكومية وبين القطاع الاقتصادي (العام والخاص) و(المجتمع الأهلي). وفي هذا البحث وللإجابة عن التساؤل الهام حول قدرة هذه السلطات على تحقيق أهداف التنمية المستدامة, تم تحليل الواقع على المستويات المؤسسية والتشريعية والمالية إلى أن تم التوصل إلى العديد من الاستنتاجات والمقترحات الكفيلة بتفعيل عمل السلطات المحلية بمختلف مستوياتها لتحقيق الأهداف التنموية المرجوة. In Stockholm conference, 1972, and the Earth conferences that followed, the United Nations stressed on the dialectic attachment between economic development and environmental balance. In those conferences, Syria undertook to set national plans in the field of sustainable environment and development called Local Agenda 2, the achievement of which requires planning and development integrity, and the most important of which are flexible and transparent cooperation and partnership among local administrative governmental authorities and departments or regional and central ones, between the public and private economic sectors and the civil society. In this research, and in order to answer the important question on the ability of these authorities to achieve the goals of sustainable development, the situation was analyzed at the institutional, legislative and financial levels so that we have reached a number of conclusions and suggestions which guarantee the activation of local authority function at different levels to achieve the desirable developmental goals.